The permeability of educational and socialization spheres: The example of youth volunteering - Weber Guisan, Saskia; Cortessis, Sandrine (Swiss Journal of Educational Research, 2017)
This article is based on the results of a research on competence development among 16 to 25 years old volunteers. The corpus of this qualitative research includes the transcriptions of 41 semi-structured interviews. This contribution proposes to use the notions of alternating between spheres, otherness, astonishment and boundary crossing in order to understand the place and the role that volunteering takes within the other spheres of young people lives. We analyse nine interviews taken from this corpus to understand the way in which these young people establish connections and permeability between their voluntary work sphere, their educational sphere and their professional sphere, or rather erect barriers between these spheres. Results show that under certain conditions, voluntary work can be considered as an informal learning situation offering resources in terms of competence development, identity construction and self-projection.